Induction of Heme Oxygenase-1 Attenuates the Severity of Sepsis in a Non-Surgical Preterm Mouse Model. Issue 2 (February 2017) - Fujioka, Kazumichi; Kalish, Flora; Zhao, Hui; Lu, Sabrina; Wong, Stephanie; Wong, Ronald J.; Stevenson, David K.
Abstract : ABSTRACT: Preterm sepsis is characterized by systemic bacterial invasion and inflammatory response. Its pathogenesis is unclear due to lack of proper animal models. Heme oxygenase-1 (HO-1) can affect physiologic and pathologic conditions through its anti-inflammatory, antioxidative, and anti-apoptotic properties. Since HO-1 is developmentally regulated, it may play a role in the pathogenesis of preterm sepsis. For this study, sepsis was induced using the non-surgical "cecal slurry" (CS) model. CS was given intraperitoneally at various doses to 4-day-old newborn mice to determine dose-dependent effects. The LD40 was then given and changes in bodyweight, bacterial colonization of organs, hematology, serum biochemistry, and immunomodulatory gene expression were determined. We found a dose-dependent mortality with an LD40 of 2.0 mg/g. Significant bacterial colonization and hematological changes (leukocytopenia, thrombocytopenia, and lymphocytopenia) and increased gene expression of pro-inflammatory cytokines, pattern-recognition receptors, and other genes related to immune responses were also observed. Twenty-four hours post-sepsis induction, bodyweight loss was associated with mortality and organ damage. Finally, to elucidate a protective role of HO-1, 30-μmol heme/kg was given subcutaneously 24 h pre-sepsis induction. HO activity in livers and spleens significantly increased 64% and 50% over age-matched controls 24 h post-heme administration. Importantly, heme significantly reduced mortality from 40.9% to 6.3% ( P  <0.005) and gene expression of pro-inflammatory cytokines (Ccl5, Cxcl10, IL-1b, and Ifng). We conclude that the CS model can be used as a model to study preterm sepsis. Because induction of HO-1 significantly reduced mortality, we speculate that HO-1 may confer protection against sepsis in preterm infants.